2020
DOI: 10.38212/2224-6614.2675
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of furostanol and spirostanol glycosides in Taiwanese yam (Dioscorea spp.) cultivars by high performance liquid chromatography

Abstract: A high-performance liquid chromatographic (HPLC) method was developed for the simultaneous determination of the steroidal saponins, furostanol and spirostanol glycosides, in Taiwanese yam cultivars. C18 column kept at 45 was used as the stationary phase, the mobile phase was a binary solvent system consisting of methanol and deionized water (62/38, v/v) in the first 20 min and 71/29 (v/v) from 21 to 65 min at a flow rate of 1 ml/min. Both evaporative light scattering detector (ELSD) and UV (203 to 215 nm) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The detector routinely applied in the HPLC analysis of saponins is ELSD (18-20) since it is known to be universal and sensitive, while the use of a UV detector is inadvisable due to the lack of chromophores in saponin molecules. However, some authors observed separation of saponins by employing UV detection at low wavelengths in a range of 200-210 nm (25,26).…”
Section: Hplc-elsd-esi-ms Separationmentioning
confidence: 99%
“…The detector routinely applied in the HPLC analysis of saponins is ELSD (18-20) since it is known to be universal and sensitive, while the use of a UV detector is inadvisable due to the lack of chromophores in saponin molecules. However, some authors observed separation of saponins by employing UV detection at low wavelengths in a range of 200-210 nm (25,26).…”
Section: Hplc-elsd-esi-ms Separationmentioning
confidence: 99%
“…Some of the nutrients contained in Dioscorea species are carbohydrate, essential amino acid, mineral, polyphenol, mucin (Glycoproteins), purin derivatives (eg Alantoin) and steroid saponins. [1][2][3][4][5][6][7][8][9][10] Dioscorea alata L. contained diosgenin 11 which is the major aglycone of steroid saponin acting as an intermediate steroid in the pharmaceutical industry. Steroid saponin is the most important bioactive compound due to its several biological functions, such as anticarcinogenic, antithrombotic, antiviral, hemolytic, hypocholesterolemia, hypoglycemic, immunostimulatory, antitumorigenic, anti-mutagenic, immunomodulatory and anti-inflammatory depending on its structure.…”
Section: Introductionmentioning
confidence: 99%
“…Steroid saponin is the most important bioactive compound due to its several biological functions, such as anticarcinogenic, antithrombotic, antiviral, hemolytic, hypocholesterolemia, hypoglycemic, immunostimulatory, antitumorigenic, anti-mutagenic, immunomodulatory and anti-inflammatory depending on its structure. [6][7][8][9] This article aims to find the potency of steroid saponin in purple yam tuber (Dioscorea alata L.) as an immunomodulatory agent.…”
Section: Introductionmentioning
confidence: 99%
“…As Ferreira 2011 showed a relationship of mature leaves with temperature (r=0.97) and it totally fits our data that preceding age. Yang et al, 2003; confirmed the complex relation and interference on the saponin concentration. The highest observed concentration was noted at dose of 300 kg ha -1 N (51.65) at 20 cm.…”
Section: Saponinmentioning
confidence: 60%